Paper beads a new material for interior treatments - De los Reyes, Ma. Jeizelle S.; Mayo, Adelaida Villaraza (1991.)
When we were asked to think of possible topics for our Baby Thesis, I have decided and told myself that I want my Thesis to produce something concrete and can be really of use. I was able to think of many possible materials that can be developed into something, until I remembered the concept of the beautiful beads. The main aim of the study is to be able to produce something useful, creative, cheap, and can easily be done by anyone. The paper beads, I believe, meet this aim. With the use of prototype, it is proven that it is possible for this old craft to be used as a material for interior treatment. The interior treatments that the study achieved are window treatment, room divider, and wall accessory. Even though the prototype was much exposed to sunlight and moisture, the colours and the strength of each bead did not alter. It was still in the 1970's when a friend of the family gave a choker to my mother made of paper beads. Until now, the choker is still very much intact and its colour have not changed drastically. The study formally introduces a craft which is not new but has many possibilities to create functional and decorative things for homes especially. It can be a money making hobby since its capital can be small and its process is relatively simple.
Thesis (BID)--University of the Philippines Diliman.
Keywords: Paper beads